Antimicrobial Evaluation of Bacterial Isolates from Urine Specimen of Patients with Complaints of Urinary Tract Infections in Awka, Nigeria - Perpetua A. Ekwealor; Malachy C. Ugwu; Ifeanyi Ezeobi; George Amalukwe; Belinda C. Ugwu; Ugochukwu Okezie; Catherine Stanley; Charles Esimone (International Journal of Microbiology)
Urinary tract infections (UTIs) account for one of the major reasons for most hospital visits and the determination of the antimicrobial susceptibility patterns of uropathogens will help to guide physicians on the best choice of antibiotics to recommend to affected patients. This study is designed to isolate, characterize, and determine the antimicrobial susceptibility patterns of the pathogens associated with UTI in Anambra State Teaching Hospital, Amaku, Anambra State, Nigeria. Clean catch urine samples of inpatient and outpatient cases of UTI were collected and bacteriologically analyzed using standard microbiological procedures. Antibiogram was done by the Kirby-Bauer disc diffusion method. The most prevalent isolates were S. aureus (28%), E. coli (24.6%), and S. saprophyticus (20%). The antibacterial activities of the tested agents were in the order of Augmentin < Ceftazidime < Cefuroxime < Cefixime < Gentamicin < Ofloxacin < Ciprofloxacin < Nitrofurantoin. It was found that all the organisms were susceptible in varying degrees to Nitrofurantoin, Ciprofloxacin, and Ofloxacin. It was also observed that all the bacterial species except Streptococcus spp. have a Multiple Antibiotic Resistance Index (MARI) greater than 0.2. For empiric treatment of UTIs in Awka locality, Nitrofurantoin, Ciprofloxacin, and Ofloxacin are the first line of choice.